Growth modeling in complex forest systems: CORKFITS a tree spatial growth model for cork oak woodlands - Ribeiro, Nuno Almeida (2012)
Cork oak (Quercus suber L.) woodlands (montado) consist of a multifunctional forest system that covers about 713,000 ha in Portugal. Today, its importance stems from cork production, with Portugal producing half of the cork in the world. As the main economic objectives may change with changes in markets and environment conservation concerns (e.g. biodiversity, water, carbon) there is a need for improved management tools. Spatial tree growth simulators are tools that enable the generation of tree growth scenarios dependent on site and competition status, that allow to simulate large scope management actions. In the present work it is presented a cork oak tree spatial growth simulator, CORKFITS, that was constructed with data generated by the monitoring system installed in 1995. The simulator was built assuming the potential increment modifier principle: z = zpot * modifier + ε, where zpot is the potential growth as function of site; modifier is the reduction factor as function of spatial competition index and the intensity of debark; ε is a random error. CORKFITS is composed by sub growth models (cork, stem, tree height and crown), cork production models and mortality models. Single trees are in cork oak woodlands subjected to natural (genetics and competition) and artificial (debark, crown pruning, root pruning) factors that affects their growth therefore there is a large amount of unexplained variability which creates problems in the modeling phase, the solutions for these problems will be discussed in the present work.